INTERNAL AND EXTERNAL FACTORS RELATED TO THE IMPLEMENTATION OF PATIENT SAFETY GOALS: A LITERATURE REVIEW - Astarini, Made Indra Ayu; Lilyana, Maria Theresia Arie (Nurse and Holistic Care, 2021)
Background: Patient safety goals are important things that must be done by nurses to get a patient safety culture. Individual internal factors and external factors can influence nurses in carrying out patient safety goals. Objective: This literature review study aims to discuss further internal and external factors that correlated in implementing patient safety goals by nurses. Methods: The design used was literature review. The keywords are in two languages. The keywords for articles in Indonesian are “faktor yang mempengaruhi”, “sasaran keselamatan pasien”, “perawat”, “rumah sakit”. The keywords for English articles are "factor", "patient safety goals", "Nurse", “hospital”. There was conducted through three databases, including PubMed (13 articles), Google Scholar (482 articles in Bahasa), and Science Direct (110 articles). Articles limited from January 2015 to October 2021. Then the author re-sorted the articles according were free access and full text, in the form of original articles. Result: There are 8 articles that appropriate with the criteria. Six articles are quantitative studies with a cross sectional approach and 2 articles with the SEM method. The results of the review show that there are 2 factors. Internal factors that correlated are motivation, knowledge and length of work. External factors that correlate are supervision and organizational culture. Conclusion: Two factors correlated with patient safety goals implementation by Nurses. Further research that can be carried out as a follow-up study from this literature review is to determine interventions related to these two factors to achieve the maximum application of patient safety goals.